2005
DOI: 10.1074/jbc.m413816200
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Mitochondrial Import and Assembly Pathway for Human Tom40

Abstract: Tom40 is the channel-forming subunit of the translocase of the mitochondrial outer membrane (TOM complex), essential for protein import into mitochondria. Tom40 is synthesized in the cytosol and contains information for its mitochondrial targeting and assembly. A number of stable import intermediates have been identified for Tom40 precursors in fungi, the first being an association with the sorting and assembly machinery (SAM) of the outer membrane. By examining the import pathway of human Tom40, we have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
144
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(150 citation statements)
references
References 60 publications
5
144
0
1
Order By: Relevance
“…Mitochondrial isolation and carbonate extraction using 100 mM Na 2 CO 3 , pH 11.5, were performed as described previously (5,11,22). For opening of the OMM, freshly prepared mitochondria were incubated in isotonic (250 mM sucrose, 1 mM EDTA, 10 mM Tris, pH 7.6) or hypotonic (1 mM EDTA, 10 mM Tris, pH 7.6) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial isolation and carbonate extraction using 100 mM Na 2 CO 3 , pH 11.5, were performed as described previously (5,11,22). For opening of the OMM, freshly prepared mitochondria were incubated in isotonic (250 mM sucrose, 1 mM EDTA, 10 mM Tris, pH 7.6) or hypotonic (1 mM EDTA, 10 mM Tris, pH 7.6) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that a single amino acid change in the primary sequence of Tom40 affected only transfer of preproteins to the TIM23 complex, but not to the TIM22 complex, suggested that Tom40 plays an active role in sorting proteins to the next mitochondrial translocase (47). Furthermore, a series of conserved residues near the N and C termini of the protein have been shown to be required for Tom40 assembly but not for receptor recognition (30,33,48). In this study we describe the effects of changing several regions containing conserved residues of Tom40 on the assembly, stability, and function of the TOM complex.…”
mentioning
confidence: 99%
“…The protein is essential for viability in yeast and Neurospora crassa (29,30). Based on computer analysis, Tom40 is predicted to exist as a ␤-barrel within the mitochondrial outer membrane (31)(32)(33)(34). However, computer predictions differ regarding the number and position of the ␤-strands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Homologs of yeast Tob55 are found in virtually all eukaryotes and in almost all gram-negative bacteria (Paschen et al 2003;Gentle et al 2004;Dolezal et al 2006). The group includes the bacterial Omp85/YaeT (Voulhoux et al 2003;Wu et al 2005), the plastid Toc75 (Eckart et al 2002), and the mammalian Tob55/Sam50 proteins (Humphries et al 2005). The N-terminal domain of Tob55 has been shown to recognize precursors of b-barrel proteins.…”
mentioning
confidence: 99%